Growth and Yield of Onion Alum cepa L. as Influenced by Nitrogen and Phosphorus Fertilizers Levels - hamady, M. M. El- (Canadian Journal of Agriculture and Crops, 2017)
In order to investigate the effects of different rates of nitrogen and phosphorus fertilizers on growth and yield of onion under semi-arid condition. Two field experiment was conducted during 2013/2014 and 2014/2015 seasons to study four rates of nitrogen fertilizer i.e. 72, 120, 168 and 216 kg N/ha and four rates of phosphorus fertilizer i.e. 37, 74, 111 and 148 P2O5/ha. The results clearly revealed that Highest nitrogen fertilizer rates (216 kg/ha) produced the highest values of foliage height, number of leaves/plant, foliage fresh weight, Bulbing ratio, bulb diameter and length, bulb weight, total fresh bulb weight, marketable bulb yield and TSS% in both seasons. It could be stated that increasing nitrogen fertilizer rates from 72 kg N/ha to 216 kg N/ha significantly increased foliage height, number of leaves/plant, foliage fresh weight, Bulbing ratio, bulb diameter and length, bulb weight, total fresh bulb weight, marketable bulb yield and TSS% by 4.76, 12.27, 15.9, 18.38, 15.23,11.23, 8.73, 10.21, 10.13 and 6.35 %, respectively as an average of both seasons. The results indicated that increasing phosphorus fertilizer rates from 37 kg P2O5/ha to 148 kg P2O5/ha markedly increased foliage height, number of leaves/plant, foliage fresh weight, Bulbing ratio, bulb diameter and length, bulb weight, total fresh bulb weight, marketable bulb yield and TSS% in both seasons. It could be noticed that increasing phosphorus fertilizer rates from 37 kg P2O5/ha to 148 kg P2O5/ha significantly increased number of leaves/plant, foliage fresh weight, Bulbing ratio, bulb diameter and length, bulb weight and total fresh bulb weight by 4.9, 4.14, 9.41, 4.37, 3.93,3.07 and 3.1 %, respectively as an average of both seasons. It could be concluded that the highest foliage fresh weight and bulb weight were produced by application of the highest rates from nitrogen fertilizer rate (216 kg N/ha) and phosphorus rate (148 kg P2O5/ha).